Analisis Kebisingan Lalu Lintas dan Generator Set Kampus Universitas Semarang - Fahrudin Ahmad; Roni Kartika Pramuyanti; Kukuh Wisnuaji Widiatmoko (Jurnal Teknik Sipil, 2024)
This study analyzes noise levels caused by traffic activities and generator sets (genset) in the Semarang University environment. Measurements were conducted using descriptive analytical methods by comparing measurement results against noise quality standards according to KepmenLH No.48 of 1996. Data collection was carried out in November 2023 at three location points (in front of Building V, Sports Center, and USM gate) during morning (08.00-08.30), afternoon (12.30-13.00), and evening (17.30-18.00) on weekdays and weekends. Measurement results showed traffic noise levels on weekdays reached 88.3 dB in front of the Sports Center, 85.3 dB at Building V, and 82.1 dB at the USM gate. On weekends, the highest noise level reached 82 dB. Generator noise measurements in stationary conditions reached 108.4 dB and increased to 112.4 dB during loading. The highest vehicle volume occurred during weekday evenings, reaching 3,176 vehicles/hour. Research results indicate that noise levels in the campus environment are above the permitted threshold of 55 dB for educational areas. The study recommends the construction of noise barriers and evaluation of generator placement to reduce noise impact on campus activities.